Mapping seagrass distribution in Gili Mantra National Conservation Area, Indonesia, using Sentinel 2A imagery - KHAIRUL JAMIL; MOHAMMAD ROIN NAJIH; HAWATI HAWATI; YAKUB SULEMAN; MUSTAFA MUSTAFA; AWALUDDIN AWALUDDIN; NUR RAHMANIAR; NUR AISYAH (Society for Indonesian Biodiversity, 2025)
Abstract. Jamil K, Najih MR, Hawati, Suleman Y, Mustafa, Awaluddin, Rahmaniar N, Aisyah N. 2025. Mapping seagrass distribution in Gili Mantra National Conservation Area, Indonesia, using Sentinel 2A imagery. Biodiversitas 26: 4324-4333. Indonesia, an archipelagic country dominated by coastal areas, possesses high biodiversity and abundant natural resources. Among these, seagrass ecosystems play a vital ecological role by providing habitat, supporting marine biodiversity, and stabilizing coastal sediments. Gili Trawangan Island, located in North Lombok District, West Nusa Tenggara Province, Indonesia, is surrounded by extensive seagrass beds. However, increasing anthropogenic activities have altered environmental conditions, leading to reduced water quality and degradation of coastal ecosystems, including seagrass habitats. This study aimed to assess the distribution and composition of seagrass beds on Gili Trawangan Island over the past two years. Field surveys were conducted from January to March 2024 using a quadrat-transect method, with 100 m transect lines laid perpendicular to the coastline and sampling performed with 50×50 cm2 frames at 10 m intervals. Satellite imagery from Sentinel-2A was also processed to complement field observations. Three seagrass species were recorded: Cymodocea rotundata, Thalassia hemprichii, and Halodule pinifolia. Cymodocea rotundata showed the highest density at all four sampling stations, whereas T. hemprichii exhibited the lowest. Seagrass coverage declined markedly from approximately 75 ha in 2022 to 44 ha in 2023. These findings provide essential baseline information for the sustainable conservation and management of seagrass ecosystems in Gili Trawangan.